Taxonomic review of freshwater Gammarus (Crustacea: Amphipoda) from Iran - Zamanpoore, Mehrdad; Grabowski, Michal; Poeckl, Manfred; Schiemer, Friedrich (Zootaxa, 2011)
The paper summarizes current knowledge upon taxonomy and distribution of the freshwater Gammarus Fabricius, 1775 in Iran. Based on the literature data, 24 species were recorded so far from the fresh waters in the country. Revision of previously published materials including type collections, and analysis of new materials, revealed presence of 18 valid freshwater Gammarus species in Iran (G. anodon, G. bakhteyaricus, G. baloutchi, G. crinicaudatus, G. hegmatanensis, G. komareki, G. lacustris, G. lobifer, G. loeffleri, G. lordeganensis, G. paricrenatus, G. parthicus, G. pretzmanni, G. pseudosyriacus, G. sepidannus, G. shirazinus, G. sirvannus and G. zagrosensis). Among the remaining six species, three (G. arduus, G. laticoxalis, G. syriacus) were reported as a result of misidentification and further three (G. miae, G. plumipes, G. projectus) appeared to be junior synonyms of other already described species. Distribution ranges of most of the species are restricted usually to only few localities in the mountainous terrain, so they may be treated as Iranian endemics. The only exceptions are: G. lacustris (widely distributed in Holarctic, with only few populations in Iran), G. komareki (widely distributed in the Balkan Peninsula and Asia Minor, in Iran recorded from the entire Alborz region) and G. pseudosyriacus (widely distributed in Asia Minor, in Iran found in the entire Zagros region). A brief remark on taxonomy of each species is presented, with emphasis on misidentifications, synonymies and similar species, supplemented by distribution data, and ecological details if available. An identification key for the freshwater Gammarus of Iran is provided.